Health System Readiness Management in Anticipating New Infectious Diseases and Zoonotic Threats in the Era of Global Ecological Change - Riama Vensya Sitohang (Miracle Journal Get Press, 2026)
The emergence of new infectious diseases and increasing zoonotic risks in recent decades pose serious challenges to health systems, particularly in countries with high ecological diversity and intense human-animal interactions. Global environmental changes, urban expansion, and rising human mobility amplify interspecies pathogen transmission potential. This study aims to analyze health system preparedness levels against new infectious diseases and zoonotic threats, and identify influencing factors. The research employs a mixed methods approach with a sequential explanatory design, combining quantitative and qualitative analysis. Quantitative data were gathered from surveys of 120 respondents from health institutions, laboratories, and related agencies, analyzed using descriptive statistics and multiple linear regression to test the influence of managerial capacity, One Health integration, policy support, resource availability, and ecological risk management on health system preparedness. Qualitative analysis involved in-depth interviews to reinforce statistical interpretations. Results indicate health system preparedness at a sufficient level (mean = 3.40). The regression model is simultaneously significant (R² = 0.610; p < 0.001), explaining 61% of preparedness variation by the model variables. Managerial capacity and ecological risk management are the most influential factors. Qualitative findings highlight cross-sector coordination, funding limitations, and integration of epidemiological and environmental data as primary barriers to implementing health system preparedness.